Global Trends in Organic Food Research: A Bibliometric Analysis - Astra Savero Qomara; Lissa Rosdiana Noer (Publikasi Indonesia, 2025)
The global demand for organic food has steadily increased over the past two decades, driven by growing awareness of health, environmental sustainability, and ethical production. This research examines the integration of bibliometric methodologies with the PRISMA model to identify key research trends in the field of organic food studies. The PRISMA model ensures methodological rigor by systematically mapping relevant search strings and keywords, which narrows down the vast number of articles to those directly addressing organic food and its associated dimensions. A bibliometric approach is then employed to analyze journal performance, co-authorship patterns, co-citation networks, and thematic clusters in organic food research. Results reveal a growing interest in organic food studies, with sustainability, health benefits, certification processes, and global market trends emerging as dominant themes. Notably, key clusters include discussions on alternative agriculture, the implications of climate change, and consumer behavior related to health and environmental consciousness. Thematic mapping highlights